ORGANISASI SUBAK DALAM PERSPEKTIF TEOLOGI SOSIAL - Putu Maria Ratih Anggraini (Jnanasidanta, 2021)
Subak is a water management system, rice cultivation, and the application of terracing in rice fields based on a very strong social and religious system. Subak in carrying out its organization is driven by administrators who have their respective duties and functions and all series of rice planting processions are preceded by a ritual that aims to appeal to Ida Sang Hyang Widhi Wasa in the manifestation of Dewi Sri. The worship of Dewi Sri aims for the prosperity and prosperity of rice plants or agricultural land, she is worshiped and supported by all local subak karma. There are 16 types of rituals carried out by Subak in planting rice starting from preparation for planting maintenance to harvesting.Keyword: Subak Organization, Social Theology, Dewi Sri